The Relationship between Parental Attention and Learning Achievement of Class XI MA Students AL-Hidayah Singingi Hilir - Ria Sukawati; Jumili Arianto; Gimin Gimin (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out whether there is a relationship between parental attention and the learning achievement of class XI students at MA AL-Hidayah Singingi Hilir. This research is research using associative quantitative methods with causal relationships and producing statistical data. The population in this study consisted of 63 Class XI students. The data collection instruments used were interviews, questionnaires and documentation, data processing using the IBM SPSS Version 22 application. Analysis of this research used the prerequisite test, normality test, linearity test and product moment correlation test. The results of the product moment correlation test using IBM SPSS 22 show a Pearson correlation (r) value of 0.650. Meanwhile, from the hypothesis results obtained rcount rtable or 0.650 0.244, so Ho is rejected and Ha is accepted. It can be concluded that there is a relationship between the parental attention variable and the learning achievement variable for class XI MA ALHidayah Singingi Hilir students